2015
DOI: 10.24843/spektran.2015.v03.i02.p02
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Tekan Dan Lentur Dinding Pasangan Batako Tanpa Plesteran, Dengan Plesteran Dan Dengan Perkuatan Wiremesh

Abstract: Concrete blocks are one of the common materials used in construction practice because they are quite easy to get and the price is relatively cheap. Masonry (either concrete blocks or bricks) is a structure consisting of a binding material (mortar) and a filler material (such as concrete blocks). In general, masonry is very good at resisting gravity loads, but not quite good at resisting shear loads such as loads generated by earthquakes, so it requires reinforcement in the form of plaster and additional wire m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Concrete that has excellent compressive strength is used to form a composite material and seal gaps on the bebak surface so that the wall will be wind and water resistance. Several studies examining the wall quality improvement have shown a positive synergy between the concrete composite and natural plant fiber (Mufida et al, 2018;Reis, 2006;Savastano et al, 2009), while wire mesh can increase the solidness of concrete-based walls that make them more resilient to shear forces (Anggreni et al, 2015;Purbotunggal, 2016). Meanwhile, bebak is chosen following the research framework to improve the quality of the wall material.…”
Section: Plastered Bebak As the Development Of The Composite Construcmentioning
confidence: 99%
“…Concrete that has excellent compressive strength is used to form a composite material and seal gaps on the bebak surface so that the wall will be wind and water resistance. Several studies examining the wall quality improvement have shown a positive synergy between the concrete composite and natural plant fiber (Mufida et al, 2018;Reis, 2006;Savastano et al, 2009), while wire mesh can increase the solidness of concrete-based walls that make them more resilient to shear forces (Anggreni et al, 2015;Purbotunggal, 2016). Meanwhile, bebak is chosen following the research framework to improve the quality of the wall material.…”
Section: Plastered Bebak As the Development Of The Composite Construcmentioning
confidence: 99%
“…Pada kebanyakan gedung, dinding bukanlah bagian dari elemen struktural, namun berfungsi sebagai pengaku dan penyekat atau pemisah antar ruang bangunan (Tanjung & Maidiawati, 2015). Untuk menjadikan dinding tersebut sebagai dinding struktural, adalah dengan memasang perkuatan bracing secara diagonal (Susanti, Dewi, & Nurlina, 2011), dengan memasang tulangan horizontal pada dinding yang diangkurkan ke dalam kolom (Bachroni, 2013) atau dengan menggunakan wiremesh yang kemudian dilapisi dengan plesteran (Anggreni, Sudarsana, & Sukrawa, 2015) dapat bertindak sebagai kolom praktis pada dinding.…”
Section: Pendahuluanunclassified
“…Concrete blocks are a popular building material choice in Indonesia, as they are cheap and relatively easy to obtain (Anggreni et al, 2015). Compared to clay bricks, they are often considered to be more eco-friendly, as they do not require firing treatment during the production process (Mallisa, 2011).…”
Section: Concrete Blocks As Building Materialsmentioning
confidence: 99%